Excavaciones arqueologicas en Flaviobriga. Castro Urdiales. Cantabria (1986) - Perez Gonzalez, Cesareo; Illarreguí Gomez, Emilio; Fernandez Ibañez, Carmelo (Trabalhos de Antropologia e Etnologia, 2020)
.